2021
DOI: 10.1039/d1cp02157e
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the binding mechanism of positive allosteric modulators in human metabotropic glutamate receptor 2 using molecular dynamics simulations

Abstract: Positive allosteric modulators (PAMs) of metabotropic glutamate receptor 2 (mGlu2) is well-known strategy in treatment of psychiatric disorders with the higher selectivity and lower tolerance risk. A mount of PAMs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…For similar systems with similar ligands or site-directed mutation, the entropy contribution can be omitted if only the relative order of binding affinities is of interest. 43,75…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For similar systems with similar ligands or site-directed mutation, the entropy contribution can be omitted if only the relative order of binding affinities is of interest. 43,75…”
Section: Resultsmentioning
confidence: 99%
“…For similar systems with similar ligands or site-directed mutation, the entropy contribution can be omitted if only the relative order of binding affinities is of interest. 43,75 According to the calculated binding free energies, the ability to bind in two targets for compound 3719810 was comparable. This result was consistent with its binding assays and was also verified by the molecular docking outcome, which indicated that the calculated binding energy effectively reproduced the ascending trend of experimental values.…”
Section: Pccp Papermentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, the conclusion based on single trajectories using a single algorithm can be inaccurate [ 20 ]. Furthermore, binding energy estimation using endpoint methods such as MMGBSA/MMPBSA tends to be less accurate than alchemical free energy calculation [ 63 , 64 ]. In the case of the main protease inhibitor discovery, free energy perturbation is recommended in benchmarking studies [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another important aspect about the ion channel is drug binding. MD simulations are used to explore ligand binding stability and to better assess the induced-fit effect from docking results , or to verify the binding poses from structural biology works. , Ligand-binding free energy calculations yield a quantitative profile for comparison with experimental measurements . In addition, the dynamical effects exerted by ligands can be accessed from simulation trajectories.…”
Section: Membrane Protein Simulationsmentioning
confidence: 99%